88.8k views
5 votes
Simplify the following
\sqrt[3]{343 } + (3)/(4) \sqrt[3]{ - 8}

User J Fong
by
5.3k points

1 Answer

5 votes


\sqrt[3]{343}+(3)/(4)\sqrt[3]{-8}\text{ =}(11)/(2)

Step-by-step explanation

The cube root of a number is the factor that we multiply by itself three times to get that number

so

Step 1


\sqrt[3]{343}+(3)/(4)\sqrt[3]{-8}
\begin{gathered} \sqrt[3]{343}\text{ =7} \\ because,\cdot7\cdot7\cdot7=343 \\ \end{gathered}

and


\begin{gathered} \sqrt[3]{-8}\text{ =-2} \\ \text{because -2}\cdot-2\cdot-2=-8 \end{gathered}

Step 2

replace


\begin{gathered} \sqrt[3]{343}+(3)/(4)\sqrt[3]{-8} \\ 7+(3)/(4)(-2)=7-(6)/(4)=(28-6)/(4)=(22)/(4)=(11)/(2) \end{gathered}

so,the answer is


\sqrt[3]{343}+(3)/(4)\sqrt[3]{-8}\text{ =}(11)/(2)

I hope this helps you

User Minerva
by
4.4k points